Efeito do ácido 2-cloroetilfosfônico (Ethephon) no florescimento e na frutificação do pepino (Cucumis sativus L) - Gabino Crispin Churata-Masca, Manuel; Awad, Marcel (Revista Ceres, 2025)
Two experiments were performed under greenhouse conditions to study the effects of ethephon (2-chloroethylphosphonic acid), on sex expression, growth and production of the monoecious cucumber (Cucumis sativus L.) "Aoday" cultivar. The applications were made by spraying to runoff at the seedling stage or at various other stages of plant development.